β-ecdysone/PLGA composite scaffolds promote skull defect healing in diabetic rat - Yicai Luo; Ziwei Wu; Yingjuan Zhang; Yang Qiao; Yinge Wei; Xuan Yan; Xiangyu Ma; Xianxian Huang; Xiaoxia Zhong; Zhimao Ye; Xinping Lu; Hongbing Liao (Frontiers in Bioengineering and Biotechnology)
IntroductionDiabetes mellitus often leads to bone metabolism disorders, hindering bone regeneration and delaying the healing of bone defects. β-Ecdysone, a plant-derived hormone known for its wide range of physiological activities, possesses hypoglycemic effects and promotes osteogenic differentiation. This study developed a composite PLGA slow-release scaffold loaded with β-ecdysone to enhance its bioavailability through topical administration and to investigate its potential to heal diabetic bone defects.MethodsThe composite scaffolds were fabricated using solution casting/particle leaching and freeze-drying techniques. Then a series of characterizations were subjected to test the performance of composite scaffolds, and in vitro safety of the composite scaffolds was tested by CCK8 assay and live/dead cell staining. Further, micro-CT and histology to evaluate the effect of β-E/PLGA composite scaffolds on healing of skull defects in diabetic rats at 4 and 8 weeks after implantation. Simultaneously, the safety of the scaffolds in vivo was also evaluated.ResultsThe material characterization results indicated that, in comparison to the single-pore size scaffold, the composite scaffold exhibited superior porosity, swelling ratio, drug loading capacity, and mechanical properties. Additionally, the composite scaffolds showed appropriate degradation performance and sustained drug release profiles. The CCK8 cytotoxicity assay and live/dead cell staining demonstrated that BMSCs survived and proliferated on the composite scaffold under both low-glucose and high-glucose conditions. Micro-CT and histological investigation demonstrated that β-E/PLGA composite scaffolds promoted new bone growth in the skull defect region of diabetic rats.ConclusionOverall, these findings suggest that the β-E/PLGA composite scaffolds promote the healing of bone defects in diabetic rats. The combination of β-ecdysone and tissue-engineered scaffolds presents a promising approach for treating diabetes-related bone defects.